Surface integrity study for FC300 cast iron using TiAIN ball end mill - Abu Bakar, Mohd Hadzley; Fahmi, Naim; Tamin, Norfauzi; Afuza, Anis; Izamshah, Raja; Kasim, Shahir; Mohd Amran, Mohd Amran; Shamsudin, Noorazizi; Raffi, Nurul Fatin (Malaysian Tribology Society (MYTRIBOS), 2019)
Finishing of FC300 gray cast iron predominantly done by manual polishing. Study the surface integrity of FC300 after machining is crucial to investigate the surface characteristics before polishing. This work aims to investigate the surface profiles and subsurface alterations induced by milling of FC300 gray cast iron using TiAlN Ball end mill. Machining trials were performed using CNC variaxis machine in dry condition at the cutting speeds of 66-99 m/min, feed rates of 0.27-0.42 mm/tooth and constant depth of cut of 0.1 mm. The results shows that the surface roughness decreased as the cutting speed increased from 66 m/min to 88 m/min. Smooth and shiny surface profiles appeared at the lower cutting speed of 66 m/min due to effect of lubrication layer that formed from the small fragmented graphite flakes. When the cutting speed increased to 99 m/min, surface profiles appeared with smeared and large graphite flakes probably due to higher rotational impact from the cutting tool. Analysis of subsurface microstructure observed bending effects at the region where worn cutting tool applied. Severe crack nucleation’s were evidence to reflect severe rubbing action from worn cutting tool.